ANALISA LUASAN TERUMBU KARANG DI PERAIRAN PULAU TEGAL LAMPUNG DENGAN TEKNOLOGI PENGINDERAAN JAUH - Faris Muhtar; Armijon Armijon; Fauzan Murdapa; Romi Fadly (Jurnal Geofisika Eksplorasi, 2019)
Damage to coral reefs on Tegal Island has an impact on reducing coral reef habitats, so monitoring needs to be done. Monitoring is done by analyzing the extent and changes by utilizing remote sensing technology to map the existing conditions. The data used are Landsat imagery in 1998, 2008, 2015 and 2018. Digital image processing is done starting from image correction, lyzenga algorithm calculation, image interpretation and field validation, and accuracy testing of coral reef habitats using a confusion matrix. The results showed that there was a change in the area of coral reefs from 1998 to 2018. The coral reef class experienced a reduction of 11.22 ha. Coral classes that changed into sand classes were 9.13 ha (29.49%) and seagrasses were 4.38 ha (14.15%). The class of sand that turned into coral reefs was 2.08 ha (13.52%) and seagrass classes that turned into coral reefs were 0.21 ha (0.25%). The biggest change is the change in the coral reef to sand covering an area of 9.13 ha (29.49%), while the smallest change is the change in seagrass into a coral reef covering an area of 0.21 ha (0.25%). In the other classes, the biggest change in area was seagrass change into sand covering an area of 5.76 ha (6.96%), while the smallest change was the change in the sand to seagrass covering an area of 2.67 ha (17.35%).